Democracy & Act 11 of 2008 (Chapter VII, Article 27, Paragraph 3) - Silitonga, Yudha Fernando (Journal of Applied Information, Communication and Technology, 2019)
In this study, researchers are interested to see the potential threat of Act 11 of 2008 (Chapter VII, Article 27, Paragraph 3) to the values of democracy. Act No.11 of 2008 turned out to save a potential threat to the values ​​of democracy in Indonesia. It is related to Chapter VII, Article 27, Paragraph 3 regulating defamation / or defamation. Through the article, the government can impose penalties for civil society if insulting / or defamation in cyberspace. Researchers using the method of literature study in collecting research material. In the analysis, the researchers used a model of interactive method of Miles and Huberman analysis.